Hemşirelerin kemoterapi hazırlama ve uygulama sırasında çevreyi, kendilerini ve hastaları korumaya yönelik tutumları - (:unkn) unknown (My University, 2003)
Bu araştırma kemoterapi (KT) hazırlama ve uygulama sırasında hemşirelerin çevreyi, kendilerini ve hastalan korumaya yönelik tutumlarım belirlemek amacı ile gerçekleştirilmiştir. 65 hemşirenin katıldığı araştırmada veriler 35 ifade içeren, koruyucu önlemlerin üç başlık altında (çevreye, kendine ve hastaya yönelik) gruplandırılarak yer aldığı ve her bir grubun puanının O ile 100 arasında değiştiği form ve gözlem yolu ile toplanmıştır. Sonuçların yorumlanmasında yüzdelik, ortalamalar, t, pearson korelasyon testi ve varyans analizi kullanılmıştır. Olguların %36.9'u KT konusunda özel eğitime katılmıştır. Çevreyi, kendini ve hastayı korumaya yönelik önlemlerden alınan puanlar sırasıyla 39.30$pm$6.07, 60.30$pm$17.49 ve 66.05$pm$17.36'dır. Öğrenim düzeyi yüksek olan, birimde çalışma deneyimi fazla olan ve KT eğitimi alan hemşireler KT'ye yönelik koruyucu önlemleri daha fazla almaktadırlar. Bu nedenle yüksek öğrenimli hemşirelerin KT gibi özel dallarda çalıştırılması, çalışılan servislerin sık sık değiştirilmemesi ve KT ilee ilgili özel eğitim almalarının sağlanması önerilmektedir.

The Safe Handling Practices Of Nurses Who Involve In Cytotoxic Drugs During Preparation And Administration This study was constructed to reveal the safe handling practices of 65 nurses who involve in cytotoxic drugs during preparation and administration. Data were collected by a questionnaire, which includes protective measures used: during various activities "with cytotoxic drugs and observations. The questionnaire composed of 35 items including three subdimensions (regarding to protective practice towards environment, nurse, and patient). The score for each subdimension changed between 0 to 100. percentage distribution, means, t test, Pearson',' correlation test, and variance analysis were made use of in interpreting of data. 36.9% of nurses had special education on chemotherapy Mean scores regarding to protective practices towards environment, nurses, and patients were 39.30 (SD: 26.07), 60.30 (SD: .'7.49), and 66.05 (SD: 17.36) respectively. nurses who had good educational level and more working experience in department, and attend to education program on chemotherapy had higher scores on safe handling practices than others. In conclusion we recommended that nurses who had good education should be worked in chemotherapy services, not be changed their department so often and be given opportunities to attend special education on chemotherapy.
The safe practices of nurses who involve to cytotoxic drugs during preparation and administration
Keywords: Onkoloji; Hemşirelik